Sulfur defect CdS quantum dot as well as preparation method and application thereof

CN119735233APending Publication Date: 2025-04-01GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
6 Cites 0 Cited by

Patent Information

Application Number
CN202411661724.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-04-01

Smart Images

  • Figure CN119735233A_ABST
    Figure CN119735233A_ABST
Patent Text Reader

Abstract

The invention provides a sulfur defect CdS quantum dot and a preparation method and application thereof.The preparation method of the sulfur defect CdS quantum dot comprises the steps that a sulfur source and a Cd precursor solution are mixed, and a mixed solution is obtained; under an inert atmosphere, heating the mixed solution to 100-180 DEG C, carrying out a constant temperature reaction for 0.5-3 h, cooling to 20-30 DEG C at a cooling rate of 2.5-5.5 DEG C / min, and filtering to obtain the sulfur defect CdS quantum dot, the pH value of the Cd precursor solution is greater than or equal to 10. The preparation method provided by the invention is simple in process, the sulfur defect CdS quantum dots with high catalytic activity can be obtained without precious metal catalysis, and the sulfur defect CdS quantum dots have excellent light reforming performance and hydrogen evolution activity on plastics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic nanomaterials and relates to a photocatalyst, in particular to a sulfur-deficient CdS quantum dot and a preparation method and application thereof. Background Art

[0002] Polyethylene terephthalate (PET) plastic is one of the indispensable materials in the current packaging and textile industries. Its global annual production has reached 70 million tons, but only about 20% of PET plastic waste can be recycled. A large amount of difficult-to-degrade plastic waste is landfilled or accumulated in nature, causing a waste of fossil resources and causing serious environmental pollution.

[0003] Photoreforming technology has gained wide attention as an ideal, clean and green emerging technology. This is because it uses the inexhaustible energy of sunlight to achieve continuous production of hydrogen (H2), while converting plastics such as PET, PLA, PUR into high-value-added organic chemicals (such as formates, acetates and glyoxal) at room temperature and pressure, thereby achieving the degradation and reuse of plastic waste. In order to efficiently promote the transformation of a carbon circular economy, photoreforming technology regards plastic waste as a potential carbon source, combines photocatalytic water decomposition to produce hydrogen with plastic photooxidative degradation, and provides an ideal way to turn "waste" into "treasure" to solve the problems of energy crisis and environmental pollution.

[0004] Tomoji Kawai et al. first proposed photoreforming technology in 1981. They used TiO2 / Pt photocatalyst to achieve photocatalytic decomposition of water to produce hydrogen. However, TiO2 can only absorb ultraviolet light (about 4% of the solar spectrum) and requires the use of expensive hydrogen evolution co-catalysts (such as Pt), making it difficult to promote and apply it in industry.

[0005] Cadmium sulfide (CdS) is an important II-VI semiconductor with a bandgap of 2.42eV and is widely used in the field of photoreforming plastics. In addition to absorbing ultraviolet light, CdS can also absorb visible light, and can achieve photocatalytic decomposition of water to produce hydrogen without the use of precious metal co-catalysts. Therefore, it has begun to replace TiO2 as a new hotspot in the field of photoreforming research. However, CdS prepared by existing technologies is easy to agglomerate, and the separation efficiency of photogenerated electrons and holes is low. In addition, the rapid recombination of electron-hole pairs in CdS and its own severe photocorrosion phenomenon seriously hinder the improvement of its photocatalytic efficiency.

[0006] CN111686761A discloses a Cu / CdS / graphene composite photocatalyst, which improves its photocatalytic activity and stability by introducing graphene and depositing metal nanoparticles. The ultra-large specific surface area, high conductivity and excellent carrier mobility at room temperature of graphene are utilized to improve the agglomeration of the photocatalyst, and the graphene is used as an electron transport medium to quickly separate electrons and holes, thereby improving the separation efficiency of photogenerated electrons and holes. However, the Cu / CdS / graphene composite photocatalyst needs to be catalyzed by Cu to complete the photocatalytic hydrogen production process.

[0007] CN113233495A discloses a CdS nano-ring powder. In order to solve the problem that the CdS nano-ring powder is easy to agglomerate, the CdS nano-rings need to be first dispersed in sodium carboxymethyl cellulose and sodium alginate containing groups such as -COOH and -OH to form a transparent hydrogel biofilm matrix for cross-linking, and then loaded to prepare a CdS composite film, and then the prepared CdS composite film is applied to photocatalytic degradation.

[0008] CN106732663A discloses a CdS nanosphere / Elicarb graphene (CdS-EGR) photocatalyst, which utilizes the characteristics of Elicarb graphene (EGR) such as few surface defects and high electrical conductivity to improve the photocatalytic activity of the semiconductor photo CdS catalyst.

[0009] In the prior art, the technical problem of CdS agglomeration is solved by compounding CdS with graphene or loading CdS in a matrix, which involves the preparation of graphene or matrix materials and the preparation of CdS compounded with graphene and matrix materials, making the entire preparation process cumbersome and complicated, and the photocatalytic performance of the prepared composite material is not only affected by CdS, but also by the performance of graphene or the matrix, making it difficult to ensure the stability of the photocatalytic performance of the prepared composite material.

[0010] Therefore, providing a method for preparing CdS quantum dots with simple process, no need for metal catalysis and high photocatalytic activity is of great significance for realizing the industrial application of CdS in the field of photoreforming technology. Summary of the invention

[0011] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a sulfur-defective CdS quantum dot and a preparation method and application thereof. The preparation method provided by the present invention does not require precious metal catalysis, and can obtain sulfur-defective CdS quantum dots with high catalytic activity. The sulfur-defective CdS quantum dots prepared by the present invention have good dispersibility and do not require the use of additional carriers during the application process. The sulfur-defective CdS quantum dots prepared by the present invention are zero-dimensional nanomaterials with significant quantum effects. By constructing sulfur defects, a large number of electron capture sites are formed on the surface, which enhances electron-hole separation, promotes the absorption of visible light, and improves the inhibition of the recombination of photogenerated carriers. It has excellent photoreforming performance and hydrogen evolution activity for plastics.

[0012] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0013] In a first aspect, the present invention provides a method for preparing sulfur-deficient CdS quantum dots, the preparation method comprising the following steps:

[0014] Mixing a sulfur source and a Cd precursor solution to obtain a mixed solution; heating the mixed solution to 100° C.-180° C. under an inert atmosphere, and reacting at a constant temperature for 0.5 h-3 h, cooling the mixed solution to 20° C.-30° C. at a cooling rate of 2.5° C. / min-5.5° C. / min, and filtering to obtain the sulfur-deficient CdS quantum dots;

[0015] The pH of the Cd precursor solution is ≥10.

[0016] In the present invention, the pH of the Cd precursor solution is ≥ 10, for example, it can be 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5 or 14, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] In the present invention, the cooling rate affects the concentration of sulfur defects in the sulfur-defective CdS quantum dots and the structural stability of the sulfur-defective CdS quantum dots. If the cooling rate is too slow, it will lead to excessive sulfur vacancies, excessive defect concentration, and the destruction of the lattice, making it impossible to effectively construct sulfur defects, thereby reducing the hydrogen evolution activity of the quantum dots.

[0018] In the preparation method provided by the present invention, the cooling rate is 2.5°C / min-5.5°C / min, for example, it can be 2.5°C / min, 2.7°C / min, 2.9°C / min, 3.1°C / min, 3.3°C / min, 3.5°C / min, 3.7°C / min, 3.9°C / min, 4.1°C / min, 4.3°C / min, 4.5°C / min, 4.9°C / min, 5°C / min, 5.2°C / min, 5.3°C / min, 5.4°C / min, 5.5°C / min, including but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0019] In the preparation method provided by the present invention, the mixed solution of the sulfur source and the Cd precursor solution is heated to 100°C-180°C, for example, it can be 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C, including but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] In the preparation method provided by the present invention, the reaction time is 0.5h-3h, for example, it can be 0.5h, 0.7h, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, including but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0021] In the preparation method provided by the present invention, the temperature is lowered to 20°C-30°C, for example, it can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] The preparation method provided by the present invention does not require the addition of precious metal catalysts or toxic organic coating agents, and can achieve the preparation of sulfur-defective CdS quantum dots through a simple process under normal temperature and pressure conditions, which is conducive to industrial production.

[0023] Preferably, the sulfur source comprises one or a combination of at least two of sodium sulfide, sodium sulfate, thioacetamide or sulfur powder. Typical but non-limiting combinations include a combination of sodium sulfide and sodium sulfate, a combination of sodium sulfide and thioacetamide, a combination of sodium sulfide and sulfur powder, a combination of sodium sulfate and thioacetamide, a combination of sodium sulfate and sulfur powder, a combination of thioacetamide and sulfur powder, a combination of sodium sulfide, sodium sulfate and thioacetamide, a combination of sodium sulfide, sodium sulfate and sulfur powder, a combination of sodium sulfide, thioacetamide and sulfur powder, a combination of sodium sulfate, thioacetamide and sulfur powder, and a combination of sodium sulfide, sodium sulfate, thioacetamide and sulfur powder.

[0024] Preferably, the Cd precursor solution comprises a cadmium source and a coating agent.

[0025] Preferably, the method of adjusting the pH of the Cd precursor solution includes: adding an alkaline solution with a mass fraction of 25%-35%, and the mass fraction of the alkaline solution can be, for example, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35%, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] The alkaline substance in the alkaline solution includes NaOH and / or KOH.

[0027] Preferably, the cadmium source comprises one or a combination of at least two of cadmium chloride, cadmium nitrate, cadmium sulfate or cadmium acetate, typical but non-limiting combinations include a combination of cadmium chloride and cadmium nitrate, a combination of cadmium chloride and cadmium sulfate, a combination of cadmium chloride and cadmium acetate, a combination of cadmium nitrate and cadmium sulfate, a combination of cadmium sulfate and cadmium acetate, a combination of cadmium chloride, cadmium nitrate and cadmium sulfate, a combination of cadmium nitrate, cadmium sulfate and cadmium acetate, a combination of cadmium chloride, cadmium nitrate and cadmium acetate, and a combination of cadmium chloride, cadmium nitrate, cadmium sulfate and cadmium acetate.

[0028] In the present invention, the introduction of a specific capping agent can adjust the stability of sulfur-defective CdS quantum dots, prevent agglomeration, and improve the dispersibility of sulfur-defective CdS quantum dots. Moreover, sulfur defects can also serve as anchoring points of the capping agent, further improving the stability of sulfur-defective CdS quantum dots.

[0029] Preferably, the coating agent comprises one or a combination of at least two of thioglycolic acid, mercaptoethanol or 3-mercaptopropionic acid, typical but non-limiting combinations include a combination of thioglycolic acid and mercaptoethanol, a combination of thioglycolic acid and 3-mercaptopropionic acid, a combination of mercaptoethanol and 3-mercaptopropionic acid, and a combination of thioglycolic acid, mercaptoethanol and 3-mercaptopropionic acid.

[0030] Preferably, the molar ratio of the cadmium source to the coating agent is (50-70):1, for example, it can be 50:1, 52:1, 54:1, 56:1, 58:1, 60:1, 62:1, 64:1, 66:1, 68:1 or 70:1, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably (55-65):1.

[0031] In the present invention, a suitable Cd precursor solution concentration is conducive to controlling the nucleation and growth of sulfur-defective CdS quantum dots, thereby obtaining sulfur-defective CdS quantum dots with uniform size and excellent performance. If the concentration of the Cd precursor solution is too high, it may cause the nucleation rate to be too fast, causing the particle size of the sulfur-defective CdS quantum dots to increase and become unevenly distributed, thereby causing aggregation and affecting the hydrogen production activity of the quantum dots. If the concentration of the Cd precursor solution is too low, the nucleation rate is insufficient, and a sufficient number of sulfur-defective CdS quantum dots cannot be effectively generated, resulting in a decrease in yield, and the size of the sulfur-defective CdS quantum dots is difficult to control and the performance is unstable.

[0032] Preferably, in the Cd precursor solution, the molar concentration of the cadmium source is 0.03mol / L-0.08mol / L, for example, it can be 0.03mol / L, 0.035mol / L, 0.04mol / L, 0.045mol / L, 0.05mol / L, 0.055mol / L, 0.06mol / L, 0.065mol / L, 0.07mol / L, 0.075mol / L or 0.08mol / L, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In the present invention, the molar ratio of the cadmium source to the sulfur source affects the relative concentration of sulfur defects in the sulfur-defective CdS quantum dots. If the molar ratio of the cadmium source to the sulfur source is too small, the relative concentration of sulfur defects in the sulfur-defective CdS quantum dots is too low, which is not conducive to the increase of photocatalytic active sites and the improvement of charge separation efficiency. If the molar ratio of the cadmium source to the sulfur source is too large, the relative concentration of sulfur defects in the sulfur-defective CdS quantum dots is too high, which is not conducive to improving the photocatalytic performance and structural stability of the sulfur-defective CdS quantum dots.

[0034] Preferably, the molar ratio of the cadmium source to the sulfur source in the mixed solution is 1:(0.5-1), for example, it can be 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.85, 1:0.9, 1:0.95 or 1:1, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] Preferably, the gas used for the inert atmosphere includes N2 and / or an inert gas.

[0036] Preferably, the inert gas includes any one of argon, helium or neon, or a combination of at least two of them.

[0037] Preferably, the method for preparing the mixed solution of the sulfur source and the Cd precursor solution comprises:

[0038] Under stirring, a sulfur source is added to the Cd precursor solution.

[0039] In the present invention, a sulfur source is added to a Cd precursor solution under stirring, which is beneficial to the uniform dispersion of the sulfur source and promotes the full reaction of the Cd source and the S source, thereby achieving uniform nucleation and growth of sulfur-deficient CdS quantum dots, and then accurately controlling the concentration and distribution of sulfur defects, thereby improving the photocatalytic activity and structural stability of the sulfur-deficient CdS quantum dots.

[0040] Preferably, the preparation method further comprises washing and drying the sulfur-deficient CdS quantum dots.

[0041] Preferably, the washing comprises washing three times with a washing solution.

[0042] Preferably, the washing liquid comprises water and ethanol.

[0043] Preferably, in the washing liquid, the volume ratio of water to ethanol is (0.5-2):1, for example, it can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2:1, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] Preferably, the washing method comprises centrifugation.

[0045] Preferably, the drying temperature is 60°C-90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] Preferably, the drying time is 5 h-10 h, for example, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In a second aspect, the present invention provides a sulfur-deficient CdS quantum dot, which is prepared by the preparation method described in the first aspect.

[0048] Preferably, the sulfur-deficient CdS quantum dots provided by the present invention are zero-dimensional nanomaterials.

[0049] The sulfur-defective CdS quantum dots in the present invention are zero-dimensional nanomaterials, which exhibit significant quantum effects and are more conducive to the directional transmission and migration of photogenerated carriers. Through the construction of sulfur defects, a large number of defects are formed on the surface as electron capture sites, which enhance electron-hole separation, promote the absorption of visible light, and improve the inhibition of the recombination of photogenerated carriers, thereby exhibiting excellent photoreforming performance and hydrogen evolution activity.

[0050] Preferably, the sulfur-deficient CdS quantum dots have a mesoporous structure.

[0051] Preferably, the average particle size D of the sulfur-deficient CdS quantum dots is less than 10 nm, for example, it can be 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm or 9.5 nm, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] Preferably, the average particle size D of the sulfur-deficient CdS quantum dots is 2 nm-4 nm.

[0053] Preferably, the specific surface area of ​​the sulfur-deficient CdS quantum dots is 48 m 2 / g-76m 2 / g, for example, it can be 48m 2 / g, 49m 2 / g, 50m 2 / g, 51m 2 / g, 52m 2 / g, 53m 2 / g, 54m 2 / g, 55m 2 / g, 56m 2 / g, 57m 2 / g, 58m 2 / g, 59m 2 / g, 60m 2 / g, 61m 2 / g, 62m 2 / g, 63m 2 / g, 64m 2 / g, 65m 2 / g, 66m 2 / g, 67m 2 / g, 68m 2 / g, 69m 2 / g, 70m 2 / g, 71m 2 / g, 72m 2 / g, 73m 2 / g, 74m2 / g, 75m 2 / g or 76m 2 / g, including but not limited to the listed values, other values ​​not listed in the numerical range are also applicable.

[0054] The sulfur-deficient CdS quantum dots provided by the present invention have a large specific surface area, can expose more active sites, and further improve the catalytic activity of the sulfur-deficient CdS quantum dots.

[0055] In a third aspect, the present invention provides an application of the sulfur-deficient CdS quantum dots as described in the second aspect, wherein the sulfur-deficient CdS quantum dots are used for photoreforming plastics or producing hydrogen.

[0056] The sulfur-deficient CdS quantum dots provided by the invention have excellent photoreforming performance and hydrogen evolution activity for plastics.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] (1) The present invention realizes the preparation of sulfur-deficient CdS quantum dots through a simple process at room temperature and pressure without adding precious metal catalysts or toxic organic coating agents, which is conducive to industrial production.

[0059] (2) The sulfur-defective CdS quantum dots in the present invention are zero-dimensional nanomaterials that exhibit significant quantum effects and are more conducive to the directional transmission and migration of photogenerated carriers. Through the construction of sulfur defects, a large number of defects are formed on the surface as electron capture sites, which enhance electron-hole separation, promote the absorption of visible light, and improve the inhibition of the recombination of photogenerated carriers, thereby having excellent photoreforming performance and hydrogen evolution activity.

[0060] (3) The sulfur-deficient CdS quantum dots prepared by the present invention have high catalytic activity and good dispersibility, and are applied in the field of photoreforming plastic technology, and have excellent photoreforming performance and hydrogen evolution activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 1 is the XRD diagram of sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0062] Figure 2 It is the IR graph of sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0063] Figure 3 This is the XPS valence band spectrum of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0064] Figure 4 This is the MS image of the sulfur-deficient CdS quantum dots prepared in Example 1 of the present invention.

[0065] Figure 5 This is the MS image of the sulfur-deficient CdS quantum dots prepared in Example 2 of the present invention.

[0066] Figure 6 This is the MS image of the sulfur-deficient CdS quantum dots prepared in Example 3 of the present invention.

[0067] Figure 7 This is the MS image of the sulfur-deficient CdS quantum dots prepared in Example 4 of the present invention.

[0068] Figure 8 It is the Raman graph of sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0069] Fig. 9 This is the solid-state EPR signal of the sulfur-deficient CdS quantum dots prepared in Example 1 of the present invention.

[0070] Fig.10 This is the solid-state EPR signal of the sulfur-deficient CdS quantum dots prepared in Example 2 of the present invention.

[0071] Fig.11 This is the solid-state EPR signal of the sulfur-deficient CdS quantum dots prepared in Example 3 of the present invention.

[0072] Fig.12 This is the solid-state EPR signal of the sulfur-deficient CdS quantum dots prepared in Example 4 of the present invention.

[0073] Fig.13 1 is the XPS spectrum of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0074] Fig.14 The Cd 3d XPS spectra of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention are

[0075] Fig.15 The S2p XPS spectra of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention are

[0076] Fig.16 This is a particle size distribution diagram of sulfur-deficient CdS quantum dots prepared in Example 1 of the present invention.

[0077] Fig.17 This is a particle size distribution diagram of sulfur-deficient CdS quantum dots prepared in Example 2 of the present invention.

[0078] Fig.18 This is a particle size distribution diagram of sulfur-deficient CdS quantum dots prepared in Example 3 of the present invention.

[0079] Fig.19 This is a particle size distribution diagram of sulfur-deficient CdS quantum dots prepared in Example 4 of the present invention.

[0080] Fig. 20 It is a TEM image of sulfur-deficient CdS quantum dots prepared in Example 1 of the present invention and a corresponding selected area electron diffraction image.

[0081] Fig.21 It is a TEM image of sulfur-deficient CdS quantum dots prepared in Example 2 of the present invention and a corresponding selected area electron diffraction image.

[0082] Fig. 22 It is a TEM image of sulfur-deficient CdS quantum dots prepared in Example 3 of the present invention and a corresponding selected area electron diffraction image.

[0083] Fig.23 It is a TEM image of sulfur-deficient CdS quantum dots prepared in Example 4 of the present invention and a corresponding selected area electron diffraction image.

[0084] Fig.24 This is a mapping diagram of the sulfur-defective CdS quantum dots prepared in Example 1 of the present invention.

[0085] Fig.25 It is the N2 adsorption / desorption isotherm of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0086] Fig.26 This is a pore size distribution diagram of sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0087] Fig. 27 It is the ultraviolet-visible diffuse reflectance image of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0088] Fig.28 The Tauc diagram corresponding to the ultraviolet-visible diffuse reflectance of the sulfur-defective CdS quantum dots prepared in Examples 1 to 4 of the present invention is

[0089] Fig.29 PL spectra of sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0090] Fig.30 This is the fluorescence lifetime decay curve of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0091] Fig.31 3 and 4 are EIS graphs of sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0092] Fig.32 It is the It diagram of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0093] Fig.33 It is the hydroxyl radical capture EPR signal of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 of the present invention.

[0094] Fig.34 The superoxide radicals (·O 2- ) to capture the EPR signal. DETAILED DESCRIPTION

[0095] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0096] Example 1

[0097] This embodiment provides a method for preparing sulfur-defective CdS quantum dots, and the preparation method is as follows:

[0098] Cadmium chloride and 3-mercaptopropionic acid were dissolved in deionized water at a molar ratio of 60:1, and after being stirred evenly and fully dissolved, a clear and transparent solution with a cadmium chloride concentration of 0.05 mol / L was obtained. A 30% mass fraction of NaOH aqueous solution was added dropwise to the solution and the pH of the solution was detected until the pH of the solution was 11 to obtain a Cd precursor solution. Ar was continuously introduced into the Cd precursor solution, and sodium sulfide was added while stirring to obtain a mixed solution with a molar ratio of cadmium chloride to sodium sulfide of 1:1. The mixed solution was heated to 120°C, and after isothermal reaction at 120°C for 1 hour, it was rapidly cooled to 25°C at a cooling rate of 4.5°C / min, filtered, and the filtered product was washed 3 times with water and ethanol in a volume ratio of 1:1 by centrifugation. The washed filtered product was dried at 65°C for 6 hours to obtain sulfur-defective CdS quantum dots.

[0099] Example 2

[0100] This embodiment provides a method for preparing sulfur-defective CdS quantum dots, and the preparation method is as follows:

[0101] Cadmium sulfate and thioglycolic acid were dissolved in deionized water at a molar ratio of 50:1, and stirred evenly to fully dissolve to obtain a clear and transparent solution with a cadmium sulfate concentration of 0.03 mol / L. A 25% mass fraction of NaOH aqueous solution was added dropwise to the solution and the pH of the solution was detected until the pH of the solution was 10 to obtain a Cd precursor solution. N2 was continuously introduced into the Cd precursor solution, and sodium thiosulfate was added while stirring to obtain a mixed solution with a molar ratio of cadmium sulfate to sodium thiosulfate of 1:1. The mixed solution was heated to 100°C, and reacted at 100°C for 0.5 hours, then rapidly cooled to 20°C at a cooling rate of 2.5°C / min, filtered, and washed the filtered product 3 times with water and ethanol at a volume ratio of 0.5:1 by centrifugation. The washed filtered product was dried at 60°C for 5 hours to obtain sulfur-defective CdS quantum dots.

[0102] Example 3

[0103] This embodiment provides a method for preparing sulfur-defective CdS quantum dots, and the preparation method is as follows:

[0104] Cadmium nitrate and mercaptoethanol were dissolved in deionized water at a molar ratio of 65:1, and stirred evenly to fully dissolve to obtain a clear and transparent solution with a cadmium nitrate concentration of 0.07 mol / L. A 35% mass fraction of NaOH aqueous solution was added dropwise to the solution and the pH of the solution was detected until the pH of the solution was 12 to obtain a Cd precursor solution. Ar was continuously introduced into the Cd precursor solution, and sulfur powder was added while stirring to obtain a mixed solution with a molar ratio of cadmium nitrate to sulfur powder of 1:1. The mixed solution was heated to 150°C, and reacted at 150°C for 2 hours, then rapidly cooled to 28°C at a cooling rate of 3.5°C / min, filtered, and washed the filtered product 3 times with water and ethanol in a volume ratio of 2:1 by centrifugation. The washed filtered product was dried at 90°C for 10 hours to obtain sulfur-defective CdS quantum dots.

[0105] Example 4

[0106] This embodiment provides a method for preparing sulfur-defective CdS quantum dots, and the preparation method is as follows:

[0107] Cadmium acetate and 3-mercaptopropionic acid were dissolved in deionized water at a molar ratio of 70:1, and stirred evenly to fully dissolve to obtain a clear and transparent solution with a cadmium acetate concentration of 0.08 ml / L. A 30% mass fraction of NaOH aqueous solution was added dropwise to the solution and the pH of the solution was detected until the pH of the solution was 13 to obtain a Cd precursor solution. Ar was continuously introduced into the Cd precursor solution, and thioacetamide was added while stirring to obtain a mixed solution with a molar ratio of cadmium acetate to thioacetamide of 1:1. The mixed solution was heated to 180°C, and reacted at 180°C for 3 hours, then rapidly cooled to 30°C at a cooling rate of 5.5°C / min, filtered, and washed the filtered product 3 times with water and ethanol in a volume ratio of 1:1 by centrifugation. The washed filtered product was dried at 80°C for 9 hours to obtain sulfur-defective CdS quantum dots.

[0108] Example 5

[0109] This embodiment provides a method for preparing sulfur-deficient CdS quantum dots, which is the same as the preparation method in Example 1 except that the molar ratio of cadmium chloride to sodium sulfide in the mixed solution is 1:0.5.

[0110] Example 6

[0111] This embodiment provides a method for preparing sulfur-deficient CdS quantum dots, which is the same as the preparation method in Example 1 except that the molar ratio of cadmium chloride to sodium sulfide in the mixed solution is 1:0.8.

[0112] Example 7

[0113] This embodiment provides a method for preparing sulfur-deficient CdS quantum dots, which is the same as the preparation method in Example 1 except that the molar ratio of cadmium chloride to sodium sulfide in the mixed solution is 1:1.5.

[0114] Example 8

[0115] This embodiment provides a method for preparing sulfur-deficient CdS quantum dots, which is the same as the preparation method in Example 1 except that the molar ratio of cadmium chloride to sodium sulfide in the mixed solution is 1:2.

[0116] Example 9

[0117] This embodiment provides a method for preparing sulfur-deficient CdS quantum dots, which is the same as the preparation method in Example 1 except that the molar ratio of cadmium chloride to sodium sulfide in the mixed solution is 1:2.5.

[0118] Example 10

[0119] This embodiment provides a method for preparing sulfur-deficient CdS quantum dots, which is the same as the preparation method in Example 1 except that the molar ratio of cadmium chloride to sodium sulfide in the mixed solution is 1:3.

[0120] Comparative Example 1

[0121] This comparative example provides a method for preparing sulfur-deficient CdS quantum dots, which is the same as the preparation method in Example 1 except that the reaction is carried out at a constant temperature of 120° C. for 1 hour and then naturally cooled at 25° C.

[0122] Comparative Example 2

[0123] This comparative example provides a method for preparing sulfur-deficient CdS quantum dots, which is the same as the preparation method in Example 1 except that after isothermal reaction at 120° C. for 1 hour, the reaction is rapidly cooled to 25° C. at a cooling rate of 1° C. / min.

[0124] Comparative Example 3

[0125] This comparative example provides a method for preparing sulfur-deficient CdS quantum dots, which is the same as the preparation method in Example 1 except that after isothermal reaction at 120°C for 1 hour, the reaction is rapidly cooled to 25°C at a cooling rate of 6.5°C / min.

[0126] Comparative Example 4

[0127] This comparative example provides a method for preparing sulfur-deficient CdS quantum dots. The method is the same as the preparation method in Example 1 except that the mixed solution is heated to 90° C. and reacted at 90° C. for 1 hour.

[0128] Comparative Example 5

[0129] This comparative example provides a method for preparing sulfur-deficient CdS quantum dots, which is the same as the preparation method of Example 1 except that the mixed solution is heated to 200° C. and reacted at 200° C. for 1 hour.

[0130] The elemental composition of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 10 and Comparative Examples 1 to 5 was quantitatively analyzed by X-ray photoelectron spectroscopy (XPS) and inductively coupled plasma atomic emission spectroscopy (ICP-OES). The analysis results are shown in Table 1.

[0131] The sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 were subjected to X-ray photoelectron spectroscopy test (XPS), X-ray diffraction test (XRD), infrared spectroscopy test (IR), model Schottky test (MS), Raman test (Raman), electron paramagnetic resonance test (EPR), particle size distribution test, TEM test, specific surface area test, UV-visible diffuse reflectance spectroscopy test, PL spectroscopy test, fluorescence lifetime decay test, EIS test and photocurrent test, respectively.

[0132] Table 1

[0133] XPS test Cd:S value ICP-OES test Cd:S value Example 1 1:0.57 1:0.89 Example 2 1:0.66 1:0.93 Example 3 1:0.76 1:0.94 Example 4 1:0.71 1:0.93 Example 5 1:0.44 1:0.39 Example 6 1:0.75 1:0.51 Example 7 1:02 1:02 Example 8 1:0.98 1:1.09 Example 9 1:1.02 1:1.18 Example 10 1:1.09 1:1.21 Comparative Example 1 1:0.64 1:0.86 Comparative Example 2 1:0.68 1:0.87 Comparative Example 3 1:0.82 1:0.95 Comparative Example 4 1:0.72 1:0.88 Comparative Example 5 1:0.71 1:0.92

[0134] According to the data in Table 1, in the sulfur-defect quantum dots prepared according to the present invention, the molar ratio of the S element is less than 1, that is, the construction of sulfur defects is successfully achieved.

[0135] like Figure 1 As shown in the XRD patterns, the diffraction peaks observed at 26.71°, 44.17° and 52.06° of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 correspond to the (111), (220) and (311) crystal planes of CdS, respectively, which are the diffraction peaks of hexagonal CdS (JCPDS75-0581). Figure 2 The IR graphs shown in Figure 1 show that the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 have 1004 and 658 cm -1 Two Cd-S stretching vibration peaks.

[0136] Figure 3 In the XPS valence band spectra shown, the valence bands of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 are 2.18 eV, 2.13 eV, 1.96 eV, and 2.01 eV, respectively, all corresponding to the valence band of CdS. Figure 4-Figure 7 In the MS curve shown, the three different frequencies intersect at one point to obtain the corresponding flat band potential. The flat band potentials of the sulfur-defective CdS quantum dots prepared in Examples 1 to 4 are -0.67 eV, -0.66 eV, -0.89 eV, and -0.72 eV, respectively, which also correspond to the flat band potential of CdS. The above proves that the present invention successfully prepared CdS quantum dots.

[0137] like Figure 8 The Raman graphs shown in Figure 1 show that the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 have a Raman value of 302 cm -1 and 589cm -1 There are two Raman bands at 309 cm, which are attributed to the lattice longitudinal optical vibration (LO) of sulfur-deficient CdS quantum dots. -1The Raman band at 603 cm corresponds to the A1 longitudinal optical vibration (1LO) mode, and the Raman frequency shift is 603 cm -1 The Raman band at corresponds to the longitudinal optical vibration (2LO) mode. After normalizing the main peak, the I1 / I2 ratio effectively characterizes the relative concentration of sulfur defects in different sulfur-defect CdS samples. The Raman peak intensity of the sample at the defect is different from that at the perfect lattice. When there are a large number of defects, the Raman peak intensity will suddenly increase. When the sulfur source is sodium sulfide in Example 1, it has the lowest I1 / I2 ratio (I1 / I2=1.68), indicating that it has the most sulfur defects. Figure 9-12 In the solid-state EPR signal shown, the g factor is 2.004, which is the characteristic position of the S vacancy.

[0138] Figures 13 to 15 In the XPS spectra shown in FIG. 1 , the Cd 3d XPS spectra of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 can be divided into two peaks in the range of 401.5 eV-408.2 eV, belonging to Cd 3d 5 / 2 and Cd3d 3 / 2 , all shifted to lower binding energies, which is attributed to the sulfur vacancy region Cd 2+ The electron cloud density increases, and the S2p XPS spectrum is divided into two peaks in the range of 161eV-159.6eV, both belonging to S 2- Due to the different contents of sulfur defects, the S2p binding energy also shifts to different degrees. This further proves that the prepared CdS contains a large number of sulfur defects.

[0139] Since the relative sulfur defect concentrations in the sulfur-defective CdS quantum dots prepared from different sulfur sources are different, the sizes of the corresponding sulfur-defective CdS quantum dots are also different. Figure 16-Figure 19 As shown in the particle size distribution diagram, the average particle sizes of the sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 are 2.33 nm, 1.77 nm, 2.16 nm and 3.26 nm, respectively. Figure 20-23 As shown in the TEM images, Examples 1 to 4 all synthesized sulfur-defective CdS quantum dots with uniform size and good dispersion, and the selected area electron diffraction showed bright rings corresponding to the (111) crystal plane, indicating the presence of crystals at the same time, that is, the prepared sulfur-defective CdS quantum dots had a structure in which CdS crystals and sulfur defects coexisted. Fig.24 The mapping diagram of the sulfur-deficient CdS quantum dots prepared in Example 1 shows that Cd and S elements are evenly distributed on the surface of the quantum dots.

[0140] like Fig.25The N2 adsorption-desorption isotherms shown in the figure show that the sulfur-defective CdS quantum dots prepared in Examples 1 to 4 all belong to type IV isotherms. The desorption curves have obvious hysteresis, which is manifested as an H3-type hysteresis loop. Fig.26 The pore size distribution diagram shown shows that the sulfur-deficient CdS quantum dots are mesoporous materials. The sulfur-deficient CdS quantum dots prepared in Example 1 exhibit a higher specific surface area (75.8 m2 / g), indicating that the use of sodium sulfide as a sulfur source forms more sulfur defects, exposes more reaction sites, and is more conducive to enhancing the photocatalytic activity of the material.

[0141] The sulfur-deficient CdS quantum dots prepared in Examples 1 to 4 were subjected to UV-visible diffuse reflectance tests. Fig. 27 As shown in the figure, the absorption intensities of CdS quantum dot photocatalysts with different sulfur defect concentrations in the ultraviolet and visible regions are different. Fig.28 As shown in the Tauc plot, the band gap widths of Examples 1 to 4 are also somewhat different, with band gap values ​​of 2.46 eV, 2.68 eV, 2.39 eV and 2.24 eV, respectively, all within the visible light absorption range, proving that the photocatalyst prepared by the present invention has a good light absorption range.

[0142] from Fig.29 It can be seen from the PL spectrum shown in Example 1 that the recombination of photogenerated electrons and holes in the sulfur-defective CdS quantum dots is less than that in Examples 2, 3, and 4, indicating that appropriately increasing the relative concentration of sulfur defects can effectively improve the recombination of photogenerated electrons and holes and thus improve the photocatalytic performance. Fig.30 As shown in the fluorescence lifetime decay curve excited at λ=375nm, the shorter fluorescence lifetime of the sulfur-defective CdS quantum dots prepared in Example 1 also indicates that appropriately increasing the relative concentration of sulfur defects can effectively improve the photogenerated carrier separation efficiency.

[0143] Fig.31 The EIS graphs shown in FIG. 4 show that the sulfur-defective CdS quantum dots prepared in Examples 1 to 4 have a smaller charge transfer resistance, a higher transmission efficiency of photogenerated electrons and holes, and Fig.32 The It diagram shown indicates that light can promote the transmission of photogenerated electrons and holes, increase the photocurrent, and have a higher carrier transfer efficiency.

[0144] The sulfur-deficient CdS quantum dots prepared in Examples 1 to 10 and Comparative Examples 1 to 5 were applied to catalytic degradation of plastics, and the application examples were as follows:

[0145] Application Example 1

[0146] 5 mL of polyethylene terephthalate (PET) solution pretreated with alkali solution was transferred to 5 mg of sulfur-deficient CdS quantum dots prepared in Example 1, and PET was catalytically degraded under an LED light with a wavelength of 365 nm and a power density of 0.28 W / cm2, and its photoreforming hydrogen evolution activity was tested by gas chromatography (GC).

[0147] Application Example 2

[0148] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 2 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0149] Application Example 3

[0150] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 3 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0151] Application Example 4

[0152] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 4 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0153] Application Example 5

[0154] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 5 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0155] Application Example 6

[0156] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 6 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0157] Application Example 7

[0158] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 7 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0159] Application Example 8

[0160] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 8 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0161] Application Example 9

[0162] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 9 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0163] Application Example 10

[0164] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 10 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0165] Application Example 11

[0166] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 1 are added to catalyze the degradation of PLA (polylactic acid), and the other conditions are the same as those in application example 1.

[0167] Application Example 12

[0168] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 2 are added to catalyze the degradation of PLA, and the other conditions are the same as those in application example 1.

[0169] Application Example 13

[0170] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 3 are added to catalyze the degradation of PLA, and the other conditions are the same as those in application example 1.

[0171] Application Example 14

[0172] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 4 are added to catalyze the degradation of PLA, and the other conditions are the same as those in application example 1.

[0173] Application Example 15

[0174] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 1 are added to catalyze the degradation of PUR (polyurethane), and the other conditions are the same as those in application example 1.

[0175] Application Example 16

[0176] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 2 are added to catalyze the degradation of PUR, and the other conditions are the same as those in application example 1.

[0177] Application Example 17

[0178] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 3 are added to catalyze the degradation of PUR, and the other conditions are the same as those in application example 1.

[0179] Application Example 18

[0180] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in Example 4 are added to catalyze the degradation of PUR, and the other conditions are the same as those in application example 1.

[0181] Comparative application example 1

[0182] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in comparative example 1 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0183] Comparative Application Example 2

[0184] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in comparative example 2 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0185] Comparative Application Example 3

[0186] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in comparative example 3 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0187] Comparative Application Example 4

[0188] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in comparative example 4 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0189] Comparative Application Example 5

[0190] The difference between this application example and application example 1 is that 5 mg of sulfur-deficient CdS quantum dots prepared in comparative example 5 are added to catalyze the degradation of PET, and the other conditions are the same as those in application example 1.

[0191] The hydrogen evolution rates obtained in Application Examples 1 to 18 and Comparative Application Examples 1 to 5 are shown in Table 2.

[0192] Table 2

[0193]

[0194]

[0195] The sulfur-deficient CdS quantum dots prepared by the present invention are successfully applied to the fields of light-reforming plastics and hydrogen production technology, and have a catalytic degradation effect on three different plastics, PET, PLA and PUR.

[0196] According to the data comparison between Application Examples 1 to 6 and Application Examples 7 to 10, when the prepared CdS quantum dots do not contain sulfur defects, their corresponding photocatalytic performance decreases significantly.

[0197] According to the hydrogen evolution rate results of Application Example 1 and Comparative Application Example 1, if the temperature is not lowered according to the cooling rate of the present invention after heating, more structural defects, such as Cd and S vacancies and lattice distortion, will be introduced into the cadmium sulfide crystal. These defects will increase the recombination probability of carriers in the crystal and reduce the separation efficiency of photogenerated electron-hole pairs, thereby causing a decrease in the hydrogen evolution rate.

[0198] According to the hydrogen evolution rate results of Application Example 1 and Comparative Application Examples 2 to Comparative Application Examples 3, if the cooling rate after heating is too slow, more structural defects will be formed in the cadmium sulfide crystal, such as Cd and S vacancies and lattice distortion, resulting in an increase in the carrier recombination rate and a decrease in the hydrogen evolution rate. If the cooling rate is too fast, thermal stress and microcracks will be introduced into the crystal, destroying the structural stability of the crystal and affecting the effective separation of photogenerated electron-hole pairs, thereby resulting in a decrease in the hydrogen evolution rate.

[0199] According to the hydrogen evolution rate results of Application Example 1 and Comparative Application Examples 4 to Comparative Application Examples 5, if the heating temperature is too high, it will lead to excessive growth of CdS crystals, forming excessively large particles or agglomerates, resulting in a decrease in specific surface area, reducing light absorption efficiency, and thus causing a decrease in the hydrogen evolution rate. If the heating temperature is too low, it will lead to incomplete crystals or too small grains, affecting the crystal integrity and crystallinity of the material. Too small grains or incomplete crystals will lead to an increase in surface defects, increase the probability of carrier recombination, and cause a decrease in the separation efficiency of photogenerated electron-hole pairs, thereby causing a decrease in the hydrogen evolution rate.

[0200] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing sulfur-deficient CdS quantum dots, characterized in that: The preparation method comprises the following steps: Mixing a sulfur source and a Cd precursor solution to obtain a mixed solution; heating the mixed solution to 100° C.-180° C. under an inert atmosphere, and reacting at a constant temperature for 0.5 h-3 h, cooling the mixed solution to 20° C.-30° C. at a cooling rate of 2.5° C. / min-5.5° C. / min, and filtering to obtain the sulfur-deficient CdS quantum dots; The pH of the Cd precursor solution is ≥10.

2. The preparation method according to claim 1, characterized in that The sulfur source includes one or a combination of at least two of sodium sulfide, sodium sulfate, thioacetamide or sulfur powder.

3. The preparation method according to claim 1 or 2, characterized in that: The Cd precursor solution includes a cadmium source and a coating agent; Preferably, the cadmium source comprises one or a combination of at least two of cadmium chloride, cadmium nitrate, cadmium sulfate or cadmium acetate; Preferably, the coating agent comprises one or a combination of at least two of thioglycolic acid, mercaptoethanol or 3-mercaptopropionic acid.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the cadmium source to the coating agent is (50-70):1, preferably (55-65):1; Preferably, in the Cd precursor solution, the molar concentration of the cadmium source is 0.03 mol / L-0.08 mol / L; Preferably, the molar ratio of the cadmium source to the sulfur source in the mixed solution is 1:(0.5-1).

5. The preparation method according to any one of claims 1 to 4, characterized in that: The gas used in the inert atmosphere includes N2 and / or an inert gas; Preferably, the inert gas includes any one of argon, helium or neon, or a combination of at least two of them.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The mixing method includes: Under stirring, a sulfur source is added to the Cd precursor solution.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method further comprises washing and drying the sulfur-deficient CdS quantum dots; Preferably, the washing comprises washing three times with a washing solution; Preferably, the washing liquid comprises water and ethanol; Preferably, in the washing liquid, the volume ratio of water to ethanol is (0.5-2):1; Preferably, the washing method comprises centrifugation; Preferably, the drying temperature is 60°C-90°C; Preferably, the drying time is 5h-10h.

8. A sulfur-deficient CdS quantum dot, characterized in that: The sulfur-deficient CdS quantum dots are prepared by the preparation method according to any one of claims 1 to 7, and the sulfur-deficient CdS quantum dots are zero-dimensional nanomaterials.

9. The sulfur-deficient CdS quantum dot according to claim 8, characterized in that: The sulfur-deficient CdS quantum dots have a mesoporous structure; Preferably, the average particle size D of the sulfur-deficient CdS quantum dots is less than 10 nm; Preferably, the average particle size D of the sulfur-deficient CdS quantum dots is 2nm-4nm; Preferably, the specific surface area of ​​the sulfur-deficient CdS quantum dots is 48 m 2 / g-76m 2 / g.

10. An application of the sulfur-deficient CdS quantum dots as claimed in claim 8 or 9, characterized in that: The sulfur-deficient CdS quantum dots are used for photoreforming plastics or producing hydrogen.

Citation Information

Patent Citations

  • CdS nanosphere / Elicarb graphene photocatalyst and preparation method thereof

    CN106732663A

  • Cu / CdS / graphene composite photocatalyst as well as preparation method and application thereof

    CN111686761A

  • CdS nanoring and preparation method and application thereof, CdS composite membrane and preparation method and application thereof

    CN113233495A

  • Method for synthesizing quantum dot with uniform size distribution in aqueous phase

    CN101704516A

  • Preparation method of CdTe / CdS / SiO2 composite fluorescent nanoparticle

    CN102311736A